2019
DOI: 10.1111/jocd.13055
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between low‐level laser therapy and Guarana (Paullinia cupana) extract induces antioxidant, anti‐inflammatory, and anti‐apoptotic effects and promotes proliferation in dermal fibroblasts

Abstract: Background Low‐level laser therapy (LLLT) has several clinical applications; however, its benefits are not universal. Therefore, combination therapy with LLLT and extracts from the guarana (Paullinia cupana) plant may improve its effectiveness as guarana extracts exhibit anti‐aging properties. Objectives To evaluate the antioxidant, anti‐inflammatory, anti‐apoptotic, and proliferative effects of combined LLLT and guarana extract therapy on human dermal fibroblasts. Methods Human dermal fibroblasts (HFF‐1) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Although there is some level of variation between the results obtained from the three different assays employed here (MTT, neutral red, and ATP), the set of results did not reveal any relevant toxic effects. These results are in accord with those of previous studies that did not indicate toxicity associated with the supplementation of cell cultures with guarana or açai extract [ 20 , 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although there is some level of variation between the results obtained from the three different assays employed here (MTT, neutral red, and ATP), the set of results did not reveal any relevant toxic effects. These results are in accord with those of previous studies that did not indicate toxicity associated with the supplementation of cell cultures with guarana or açai extract [ 20 , 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that these fruits have an effect on the reversal of mitochondrial dysfunctional states and antiaging properties [ 16 19 ]. An investigation performed by [ 20 ] also reported that interactions between low-level laser therapy and guaraná extract present antioxidant, anti-inflammatory, and antiapoptotic effects and promote fibroblast proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that guaraná presents strong antioxidant and radical‐ scavenging properties (Maldaner et al, 2020 ; Roggia et al, 2020 ; Santana & Macedo, 2018 ; Yonekura et al, 2016 ), protective cellular and anti‐inflammatory properties (Machado et al, 2021 ), neuroprotective effect (Veloso et al, 2018 ), and anti‐aging proprieties (Arantes et al, 2018 ) An epidemiological study reported guaraná habitual consumption by older adult riverine with a lower prevalence of hypertension, obesity, and metabolic syndrome (da Costa Krewer et al, 2011 ). Yonekura et al ( 2016 ) had shown that small daily doses of guaraná (3 g) can improve oxidative stress markers in healthy subjects (Yonekura et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study using an HFF‐1 cell model demonstrated that the use of low‐level laser therapy combined with guarana extract administration (1, 3, 5, 10, or 30 μg/ml) downregulated the expression of pro‐inflammatory proteins and upregulated the expression of interleukin‐10, demonstrating its anti‐inflammatory effects and indicating that the use of guarana may improve the efficacy of this type of treatment (Maldaner et al., 2020).…”
Section: Effects On Human Healthmentioning
confidence: 99%